Do Infections Cause Oligospermia and Could Empiric Antibiotics Antiprotozoal and Antifungal Treat Oligospermia? - Dajanı, Mohammed Nabil (Gynecology Obstetrics & Reproductive Medicine, 2014)
OBJECTIVE: Previous studies have shown some factors that contribute to the idiopathic oligospermia which is not significantly enough to have a definite treatment for oligospermia. Our aim is to study the effect of fungal, trichomonal and bacterial infections as causes of oligospermia and to find possible treatment for it. STUDY DESIGN: This study was carried out prospective observational study at out-patients clinics in Amman, Jordan. Seventy five men who were diagnosed with idiopathic oligospermia were evaluated in this study. Medical history and thorough physical examination with hormonal assay and semen analysis were done before the use of antifungal, antiprotozoal and antibacterial treatment. Semen analysis with WHO regulations was used. RESULTS: We found significant increase in the semen analysis parameters of the patients compared before and after treatment. CONCLUSIONS: We have proved that idiopathic oligospermia is caused by fungal, trichomonal and bacterial infections, and treatment of these infections treats oligospermia with less probability to use IVF and also offers a great advantage for the couples to conceive.